2016
DOI: 10.1088/0957-4484/27/34/345708
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of one-dimensional diffusion and spontaneous segregation of hydrogen in single crystals of VO2

Abstract: Hydrogen intercalation in solids is common, complicated, and very difficult to monitor. In a new approach to the problem, we have studied the profile of hydrogen diffusion in singlecrystal nanobeams and plates of VO2, exploiting the fact that hydrogen doping in this material leads to visible darkening near room temperature connected with the metalinsulator transition at 65 °C. We observe hydrogen diffusion along the rutile c-axis but not perpendicular to it, making this a highly one-dimensional diffusion syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(40 reference statements)
2
8
0
Order By: Relevance
“…For example, IL gating induced MIT in VO 2 has been attributed to electrochemical reaction involving oxygen vacancies, which have been found to diffuse at least 0.5 μm along the rutile c -axis . H atoms also result in the stabilization of the metal phase down to 2 K, and the diffusion constant of H has been determined to be around 10 –10 cm 2 /s at 100 °C along the rutile c -axis and is much slower along the a -axis. , …”
mentioning
confidence: 99%
“…For example, IL gating induced MIT in VO 2 has been attributed to electrochemical reaction involving oxygen vacancies, which have been found to diffuse at least 0.5 μm along the rutile c -axis . H atoms also result in the stabilization of the metal phase down to 2 K, and the diffusion constant of H has been determined to be around 10 –10 cm 2 /s at 100 °C along the rutile c -axis and is much slower along the a -axis. , …”
mentioning
confidence: 99%
“…It was regarded that hydrogen ions diffuse directly along the c R axis of the rutile phase on the basis of a hydrogenated VO 2 nanobeam. 14,19,36 It should be noted that hydrogen diffusion behavior between the VO 2 nanobeam and the VO 2 film was different. The real hydrogen diffusion profiles in the VO 2 nanobeam depend on the energy barriers of the solid/gas interface (surface to subsurface) and inner bulk VO 2 , while for hydrogen in the VO 2 film, the hydrogen atom first overcame the sold/gas interface and then propagated along various directions in-plane (detailed discussion, Figures S14−S16 7d) first decreased and then recovered to pristine VO 2 , which could be reasonably ascribed to the polycrystalline property as displayed in Figure 7b.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it remained a noble metal catalyst and was only achieved on specific substrates due to the requirement of domain matching. In addition, according to the previous literature, it is generally regarded that hydrogen ions diffuse directly along the c R axis of the rutile phase (equal to the a M axis of the monoclinic phase). ,, However, the real hydrogen diffusion profiles in a VO 2 nanobeam depend on the energy barriers of the solid/gas interface (surface to subsurface) and inner bulk VO 2 , which determined the transversal or longitudinal diffusion. In addition, Warnick et al employed first-principles molecular dynamics simulation to conduct hydrogen diffusion and claimed that the hydrogen moved along oxygen channels ( c R axis), while Natelson et al found that hydrogen tended to form an O–H bond with the nearest neighbor oxygen and swung from one oxygen to the next oxygen with a “sin 2 ” path, not a straight path, implying the complex diffusion behaviors .…”
Section: Introductionmentioning
confidence: 99%
“…where D is carrier diffusion coefficient, J is diffusion flux, and dn/dx is the carrier concentration gradient [44]. With temperature increasing, the diffusion coefficient D and carrier concentration gradient dn/dx in the vertical direction of the film surface increased too.…”
Section: Resultsmentioning
confidence: 99%